Favoritism and Firms: Micro Evidence and Macro Implications - Zareh Asatryan; Thushyanthan Baskaran; Carlo Birkholz; David Gomtsyan (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the economic implications of regional favoritism, a form of distributive politics that redistributes resources geographically within countries. Using enterprise surveys from low- and middle-income countries, we document that firms located close to leaders' birthplaces grow substantially in sales and employment after leaders assume office. Firms in favored areas also experience increases in sales per worker, wages, and measured total factor productivity. These effects are short-lived, and operate through rising (public) demand for the non-tradable sector. We calibrate a simple structural model of resource misallocation on our estimates. This exercise implies that favoritism reduces output by 0.5% annually.
Keywords: D22; D72; O43; R11; 330; regional favoritism; firm performance; enterprise surveys; resource misallocation